â€œIDENTIFICATION ON THE MOTIVATING FACTORS OF EMPLOYEES OF PT GMF AEROASIA CENGKARENGâ€ - Wenno, Michael Alexander (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims at identifying factors that motivate employees of PT GMF AeroAsia Cengkareng to work. Qualitative descriptive method was employed in conducting this research. The data were collected through interviews with the employees of Human Capital Management department. This research utilized Frederick Herzberg’s Two-Factor theory as the basis for analyzing informant’s responses. In addition, thematic coding was used as the method of data analysis. The result of this study reveals that Herzberg’s motivating factors can motivate and positively influence the employees of PT GMF AeroAsia Cengkareng in their work.Keywords: Motivation, Two-Factor Theory, Frederick Herzberg